Experimental study of the motion characteristics of a bubble near a flexible structure with an attached air bubble. (1st September 2021) - Wang, Jiaxia; Wen, Xiaohu; Liu, Kun; Jiang, Mingzuo; Wang, Zili
Abstract: The strong coupling effect between an air bubble attached to a flexible plate and a nearby spark-generated bubble is investigated experimentally while also considering the structural deformation of the plate. Numerous interesting and complex bubble behaviors that depend strongly on the attached air bubble and deformation effect of the structure are observed with a high-speed camera. A multitude of bubble jet behaviors are observed during the two bubble pulsations, such as bubble splitting, jets away from the plate, jets toward the plate, upward and downward movement after splitting, and splitting after the coalescence of the two bubbles. Moreover, the attached air bubble can appear hemispherical, mushroom-shaped, or cup-shaped. To gain a better understanding of the interaction between the bubble and the flexible boundary, the displacement time history curves at the center point of the flexible structure and at the top and bottom vertices of the bubble are obtained. The motion response mode of the flexible plate under bubble loading is explored to summarize the deformation pattern of the flexible structure and the motion characteristics of the bubble. An air bubble attached to the flexible structure can change the motion characteristics of the spark-generated bubble to some extent. Highlights: A spark-generated bubble near a flexible structure with an attached air bubble is studied. Complex bubble behaviors depend strongly on the deformation effect of the flexible structure. The jet behavior of bubbles near the flexible plate is summarized. The motion response mode and deformation pattern of the flexible plate under bubble loading are explored.